Role of NGOs and Civil Society Organizations in Enhancing WASH Facilities in Government Schools: Lessons from Kallakurichi District, Tamil Nadu - Anushya, S.; Subramaniyan, Dr. J. (South Eastern European Journal of Public Health, 2024)
The research explores the significant role played by Non-Governmental Organizations (NGOs) and Civil Society Organizations (CSOs) in improving Water, Sanitation, and Hygiene (WASH) facilities in government schools within Kallakurichi District, Tamil Nadu. The study investigates the mechanisms through which these organizations contribute to the enhancement of WASH infrastructure, assess their impact on student health and educational outcomes, and identify the challenges and best practices in implementing such initiatives. The research highlights how NGOs and CSOs act as catalysts for change by mobilizing resources, raising awareness, and fostering community participation. Their efforts have led to significant improvements in access to clean water, sanitation facilities, and hygiene education in schools, resulting in better health, increased school attendance, and enhanced academic performance among students. The key findings indicate that collaborative efforts between these organizations, local communities, and government bodies are crucial for the sustainability of WASH initiatives. The study also identifies various challenges faced by NGOs and CSOs, including funding constraints, bureaucratic hurdles, and the need for capacity building. Lessons from the Kallakurichi District underscore the importance of multi-stakeholder partnerships, community involvement, and context-specific approaches in successfully addressing WASH issues in school settings.